The Correlation Between Self-Motivation and Interaction as Predictors of Students' Satisfaction in Blended Learning in The Post-Covid-19 - Hatmi, Hatmi; Qamariah, Zaitun; Syahid, Abdul (Edupedia Publisher, 2023)
This research study investigates the correlation between self-motivation, interaction, and satisfaction in the context of blended learning. The regression model, using self-motivation and interaction as predictors, significantly predicts satisfaction levels. The model explains approximately 74.5% of the variance in satisfaction, with self-motivation contributing 24.5% and interaction contributing 50%. The findings are based on a dataset of 57 participants, and Pearson's correlations indicate significant positive associations between self-motivation, interaction, and satisfaction. However, the study has limitations, including a small sample size and potential biases, which should be considered when interpreting the results.